TLR3 Is a Negative Regulator of Immune Responses Against Paracoccidioides brasiliensis - Jannuzzi, Grasielle Pereira; de Almeida, José Roberto Fogaça; Amarante-Mendes, Gustavo P.; Romera, Lavínia Maria Dal'Mas; Kaihami, Gilberto Hideo; Vasconcelos, José Ronnie; Ferreira, Camila Pontes; de Almeida, Sandro Rogério; Ferreira, Karen Spadari (Frontiers in Cellular and Infection Microbiology, 2019)
Toll-like receptors (TLRs) comprise the best-characterized pattern-recognition receptor (PRR) family able to activate distinct immune responses depending on the receptor/adaptor set assembled. TLRs, such as TLR2, TLR4 and TLR9, and their signaling were shown to be important in Paracoccidioides brasiliensis infections. However, the role of the endosomal TLR3 in experimental paracoccidioidomycosys remains obscure. In vitro assays, macrophages of the bone marrow of WT or TLR3-/- mice were differentiated for evaluation of their microbicidal activity. In vivo assays, WT or TLR3-/- mice were infected intratracheally with Paracoccidioides brasiliensis yeasts for investigation of the lung response type induced. The cytotoxic activity of CD8+ T cells was assessed by cytotoxicity assay. To confirm the importance of CD8+ T cells in the control of infection in the absence of tlr3, a depletion assay of these cells was performed. Here, we show for the first time that TLR3 modulate the infection against Paracoccidioides brasiliensis by dampening pro-inflammatory response, NO production, IFN+CD8+T and IL-17+CD8+T cell activation and cytotoxic function, associated with granzyme B and perforin down regulation. As conclusion, we suggest that TLR3 could be used as an escape mechanism of the fungus in an experimental paracoccidioidomycosis.